2015
DOI: 10.1139/cjm-2014-0627
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of thePDR16gene influences the plasma membrane properties of the yeastKluyveromyces lactis

Abstract: The plasma membrane is the first line of cell defense against changes in external environment, thus its integrity and functionality are of utmost importance. The plasma membrane properties depend on both its protein and lipid composition. The PDR16 gene is involved in the control of Kluyveromyces lactis susceptibility to drugs and alkali metal cations. It encodes the homologue of the major K. lactis phosphatidylinositol transfer protein Sec14p. Sec14p participates in protein secretion, regulation of lipid synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Several reports in C. albicans showed that Ca Upc2p positively regulates the expression of MDR1 gene, encoding a multidrug transporter of the major facilitator superfamily that exports azoles (Dunkel et al, 2008; Flowers et al, 2012; Znaidi et al, 2008). The observed azole sensitivity of the yeast Klupc2 deletion mutants can be the result of increased passive diffusion of azoles across the modified plasma membrane (Culakova, Dzugasova, Perzelova, Gbelska, & Subik, 2013; Goffa et al, 2014; Toth Hervay et al, 2015; van den Hazel et al, 1999) or decreased efflux of azoles from cells. On the other hand, the fact that these phenotypes are suppressed by UFAs suggests that the observed defects could be the result of altered membrane functions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several reports in C. albicans showed that Ca Upc2p positively regulates the expression of MDR1 gene, encoding a multidrug transporter of the major facilitator superfamily that exports azoles (Dunkel et al, 2008; Flowers et al, 2012; Znaidi et al, 2008). The observed azole sensitivity of the yeast Klupc2 deletion mutants can be the result of increased passive diffusion of azoles across the modified plasma membrane (Culakova, Dzugasova, Perzelova, Gbelska, & Subik, 2013; Goffa et al, 2014; Toth Hervay et al, 2015; van den Hazel et al, 1999) or decreased efflux of azoles from cells. On the other hand, the fact that these phenotypes are suppressed by UFAs suggests that the observed defects could be the result of altered membrane functions.…”
Section: Resultsmentioning
confidence: 99%
“…The excitation wavelength was 360 nm, and the emission wavelength was 430 nm. Anisotropy ( r s ) was calculated from polarized intensities as described in Toth Hervay et al (2015). For statistical analyses, the one‐way analysis of variance and post‐hoc Dunnett multiple comparisons with control were used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations